INFLUENCE OF PRINCIPAL’S LEADERSHIP ON TEACHER MOTIVATION AND PARENT’S STUDENTS SATISFACTION TOWARD THE QUALITY OF EDUCATION SERVICE IN PELANGI EDUCATIONAL INSTITUTION MEDAN - Tika Nirmala Sari (JURNAL HANDAYANI PGSD FIP UNIMED, 2019)
Abstract: In the level of Elementary School, parents took important role in making decision for their children as students. Parent’s satisfaction is worthy to consider by Educational Institution in an effort to improve quality of educational services. Principal and teacher are important components who involved in an effort to improve student’s parent satisfaction with the quality of educational services. The aim of this study was  to find out the effect of principal’s leadership, teacher’motivation and quality of education on parent’s satisfaction by path analysis technique. The result of the study showed if principal’s leadership, teacher’motivation and quality of education significantly did not effect to the parents’s satisfaction by partially and simultaneously. Altough didn’t effect significantly, but quality of education services has positively impact and correlation to student’s  parent satisfaction. Keywords: Leadership, Motivation, Service Quality, Customer Satisfaction, Path Analysis. Abstrak: Pada tingkat Sekolah Dasar, orang tua memiliki peranan yang penting dalam pengambilan  keputusan bagi anak-anak mereka selaku siswa. Kepuasan orang tua penting untuk dipertimbangkan oleh lembaga pendidikan, sebagai upaya untuk meningkatkan kualitas pelayanan pendidikan. Kepala sekolah dan guru merupakan komponen penting yang terlibat dalam upaya meningkatkan kepuasan orang tua siswa terhadap kualitas layanan pendidikan. Penelitian ini bertujuan untuk mengetahui pengaruh kepemimpinan kepala sekolah, motivasi guru dan kualitas layanan pendidikan terhadap kepuasan orang tua siswa dengan menggunakan tekhnik analisis jalur. Hasil penelitian ini menunjukkan bahwa kepemimpinan kepala sekolah, motivasi guru dan kualitas layanan pendidikan tidak berpenmgaruh secara signifikan terhadap kepuasan orang tua siswa, baik secara parsial maupun simultan.  Meskipun tidak berpengaruh secara signifikan, namun kualitas layanan pendidikan memiliki pengaruh dan hubungan yang positif terhadap kepuasan orang tua siswa. Kata Kunci: Kepemimpinan, Motivasi, Kualitas Pelayanan, Kepuasan Pelanggan, Analisis Tujuan.